PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS POWER POINT UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA KELAS II DI SDN BANYURADEN - Siti Nurul Hidayah; Urip Muhayat Wiji Wahyudi (STKIP Subang, 2025)
The purpose of this study was to determine (1) the feasibility of developing a Microsoft PowerPoint-based interactive media product for the application of the Pancasila principles (PASILA) in Pancasila Education learning for second-grade students at Banyuraden Public Elementary School (2) the practicality of the PASILA product (3) the effectiveness of PASILA media in Pancasila Education learning for second-grade students at Banyuraden Public Elementary School. The research was conducted at Banyuraden Public Elementary School. The subjects were second-grade students, and the objects were the students' learning outcomes in Pancasila Education. This research was a development research (R&D) using the Borg and Gall method, modified from Sugiyono's, and consisted of 9 stages. The results of the PASILA media development research are as follows: (1) the development product was declared suitable for use with a percentage of media experts of 85.6% and material experts of 87%. (2) the development of Pasila interactive media is practically used in learning with a student response of 80% and a teacher response of 81.3%. (3) the development of Pasila interactive media is effective in improving student learning, as seen from the increase in the average score of 32.7 and the T-test with a sig. value of 0.001. Thus, it can be concluded that the Pasila interactive learning media created is suitable, practical, and effective for use in improving student learning in grade II Pancasila Education